A cross-sectional study using the Childhood Measurement Programme for Wales to examine population-level risk factors associated with childhood obesity. Issue 11 (3rd August 2021) - Beynon, Claire; Pashayan, Nora; Fisher, Elizabeth; Hargreaves, Dougal S; Bailey, Linda; Raine, Rosalind
Abstract: Objective: The aim of this cross-sectional study was to examine the association between childhood obesity and modifiable population-level risk factors, after accounting for deprivation. Design: A review of the literature identified population-level risk factors including a healthy childcare setting, the local food environment, accessible open space, community safety and crime. Data for these risk factors were then identified and matched by each of the twenty-two local government areas in Wales to each child that had data on height and weight in the Wales Childhood Measurement Programme (CMP) (2012–2017). Multivariable logistic regression was used to identify associations with childhood obesity. Setting: The current study was undertaken in Wales, UK, where approximately one in eight 4–5-year-olds are classified as obese. Participants: All participants were children aged 4 or 5 years who attend school, measured as part of the CMP, between 2012 and 2017 ( n 129 893, mean age 5·0 (sd 0·4) years). Results: After adjusting for deprivation, small but statistically significant associations were found between childhood obesity and percentage of land available as accessible open space OR 0·981 (95 % CI: 0·973, 0·989) P < 0·001) and density of fast food outlets OR 1·002 (95 % CI 1·001, 1·004, P = 0·001). No other population-level risk factors were associated with childhood obesity. Conclusions: The current study indicates that, even after accounting for deprivation, risk factors such as the density of fast food outlets and access to green space should be considered when tackling childhood obesity as a public health issue.